Study of the synergistic effects of bioactive glasses with Manuka honey - Lippert, Jessica; Arango Ospina, Marcela; Boccaccini, Aldo R. (Open Ceramics, 2025)
Bioactive glasses (BGs) are highly researched biomaterials in the field of bone tissue engineering. Besides their good biocompatibility and biodegradability, they also develop osteogenic and angiogenic effects due to the release of several biologically active ions through the dissolution process. To further improve the functionality of BGs, different biomolecules can be added, which are then released into the body together with the BG ionic dissolution products. For this purpose, phytotherapeutic agents can be used, which have the potential advantage of inducing less undesirable side effects than synthetic drugs and can exhibit anti-inflammatory and antibacterial activity. A well-known example of such natural compounds is the Manuka honey from New Zealand, which was used in this project. The aim of this study was thus to investigate the synergistic effects of the dissolution products of bioactive glasses in combination with Manuka honey (MH). Different relevant bioactive glass compositions (45S5 BG, 13–93 BG and 0106-B1 BG) were combined with MH. Cell biology (osteoblast-like cell line MG-63) and antibacterial assays (E. coli and S. aureus) were performed. The results indicated synergistic effects of BGs and MH, particularly in relation to the antibacterial activity of BG-MH combinations, which resulted in overall bacteria viabilities of < 40% compared to 80% of viable bacteria for BG samples without MH. Interestingly, the ionic dissolution products from 13-93 BG and 0106-B1 BG showed superior effects on MG-63 cells when combined with MH compared with 45S5 BG at the same concentrations. These findings suggest that combining BGs with MH enhances the stimulatory effects on cells and bacteria, supporting the potential use of BGs in combination with natural compounds for tissue engineering applications.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Antibacterial effect; Bioactive glasses; Herbal medicine; Ionic medicine; Manuka honey; Phytotherapeutics